The study of laparoscopic cholecystectomy and its conversion to open cholecystectomy: analysis of 100 cases in Navi Mumbai, India - Narwade, Nandkishor; Shaikh, Tanveer; Jain, Rishabh; Khan, Naseem; Ghosalkar, Mithilesh; Ansari, Sharique; Sharma, Yashashvi (International Journal of Research in Medical Sciences, 2017)
Background: Laparoscopic cholecystectomy has now become a better option instead of open cholecystectomy for the treatment of cholelithiasis that is it has become a gold standard for cholelithiasis condition. Last century has been the most fruitful era for the treatment of biliary tract disease as it saw the progress from open to laparoscopic surgery with single port surgery etc. Methods: The purpose of our study is grading of Laparoscopic cholecystectomy and studying the outcome of problematic and challenging Laparoscopic cholecystectomy cases, its complication and management, to decide when to convert Laparoscopic cholecystectomy to open cholecystectomy. This study analyzes the conversion rate of laparoscopic cholecystectomy to open cholecystectomy in Navi Mumbai, India. This is a retrospective study of 100 patients conducted from October 2012 to October 2014. Results: Out of the 100 cases 98 got successfully operated by Laparoscopic cholecystectomy. Only 2 cases out of 100 got converted from Laparoscopic to open cholecystectomy and they belonged to grade E with empyema. Conclusions: Laparoscopic cholecystectomy has become the procedure of choice for management of symptomatic gall bladder. Laparoscopic cholecystectomy intra operatively for grade A to E where Grade A is very easy level of performing Gall bladder surgery to Grade E where conversion is 100% due to bad.